Application of feedforward neural network for the classification of pathological voices - Sazali, Yaacob, Prof. Dr.; Murugesa Padiyan, Paulraj, Dr.; Mohd Rizon, Mohammed Juhari, Prof. Dr.; Muthusamy, Hariharan, Dr. (Universiti Teknologi MARA (UiTM), 2011)
Organized by Universiti Teknologi MARA, 9th - 11th March 2011 at Malacca, Malaysia.